Conservation of Ancient Manuscripts in Nagari Pasia Laweh to Designate as Cultural Heritage through Documentary Film Production - Riki Rikarno; Akhyar Hanif; Novi Budiman; Siti Fadilla; Irwandi Irwandi; Andri Maijar; Mutia Aini Ahmad (Jurnal Masyarakat Religius dan Berwawasan, 2022)
The Faculty of Ushuluddin Adab and the da'wah of IAIN Batusangkar tried to conserve theancient manuscripts by documenting them in a documentary film. Rescue and security are carried out invarious ways as an effort to prevent cultural heritage objects from being damaged, destroyed or destroyed,as well as efforts to keep them from being lost. The conservation effort of ancient manuscripts, the FUADTEAM tried to document it into a documentary film with the title "GUARANTEE". Planning a production,the Production Team of the Faculty of Ushuluddin will be faced with five things at once that require deepthinking, namely production materials, production facilities (equipment), production costs (financial),production implementing organizations, and stages of production implementation